PERCUTANEOUS INTERVENTIONS FOR ACUTE ISCHEMIC HEART DISEASE WITH CORONARY BIFURCATION LESIONS - Аlimov Doniyor Anvarovich; Salakhitdinov Shukhrat Najmitdinovich; Tursunov Sardor Bakhtinurovich; Giyoszoda Laylo Bakhtiyarovna; Mirzakarimov Khayrulla Fayzullaevich; Dzhafarov Saidamir Muradovich; Alimkhanov Bekhzod Shukhratovich; Khaydarov Makhmudjon Israilovich (Utilitas Mathematica, 2025)
Bifurcation lesions in coronary arteries present a significant challenge in percutaneous coronary intervention (PCI), particularly in the setting of acute coronary syndromes (ACS). These lesions are associated with increased procedural complexity and higher rates of adverse events. This review aims to summarize current evidence regarding the optimal strategies for PCI in ACS patients with bifurcation lesions. We discuss various stenting techniques, including provisional side branch stenting, culotte stenting, crush stenting, and tap stenting, weighing the benefits and risks of each approach based on available clinical trial data. We also address the importance of intravascular imaging (IVUS or OCT) in guiding PCI and optimizing stent deployment. Finally, we highlight areas where further research is needed to improve outcomes for this challenging patient population.